Analysis of the role of Hsp90 in colon cancer and cancer stem-like cell biology in vitro using a genetically paired cell line model - Slater, Cindy (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
Colon cancers are commonly associated with mutations or changes in signaling in the Wnt/Î²-catenin pathway. Cancer treatments, such as chemotherapy and radiation, are challenged by the limited methods of disease detection and the insufficient elimination of contributing factors, such as cancer stem-like cells (CSC), to metastatic disease. CSC are characterised by their ability to survive anchorage-independently and attribute to therapeutic resistance. To examine the biological changes associated with the progression of human colon cancers and the role of Hsp90 in cancer and CSC biology, SW480 and SW620 genetically paired (isogenic) colon cancer cell lines from the same patient were characterised for populations of putative CSC, tumoursphere (TS) forming ability, cell growth, behaviour and response to anti-cancer therapeutics. The SW480 cell line was established from a primary colon adenocarcinoma and the SW620 was established from a lymph node metastasis of the primary cancer one year later. To address the role of Hsp90 in colon cancer, the sensitivity of cells and TS were analysed in response to geldanamycin and novobiocin, and an isoform-specific approach to the targeting of Hsp90Î± was developed. Flow cytometric analysis of putative CSC by phenotype revealed variable proportions of cells bearing the CD44+/CD133+ surface protein marker, widely used in the identification of colon CSC, in SW480 and SW620 cells. The paired cell lines maintained similar proportions of putative CSC, identified by the expression of the ABCG2 protein (side population; 1 %) and through high aldehyde dehydrogenase activity (ALDEFLUOR; 6 %). SW480 cells demonstrated greater TS forming efficiency than SW620 cells (49.9 and 35.5 %, respectively) and observations of wound-healing showed SW480 cells to be more migratory than SW620 cells. No difference in response to Hsp90 inhibition was observed between paired cell lines, however SW480 TS resisted treatment with geldanamycin. This the first study to report a dose-dependent increase in TS growth in response to novobiocin inhibition of Hsp90, and to demonstrate that that the sensitivity of SW480 and SW620 TS to oxaliplatin, a common drug for the treatment of metastatic colon cancers, was enhanced by novobiocin, providing promise for the elimination of CSC with combined chemotherapeutics. We analysed the Wnt/Î²-catenin pathway in response to expression of short hairpin RNA (shRNA) against Hsp90Î± or a control non-targeting shRNA, under the control of a tetracycline-responsive promoter. Hsp90Î± knockdown contributed to a deregulated stress response, presenting with reduced Hsp27 and Î²-catenin protein, but corresponded to an increase in the association between Hsp90, Î²-catenin and Hsp27 in vitro. The reduction of Hsp90Î± did not influence sensitivity of the colon cancer cells to activators or inhibitors of the Wnt pathway, but rather correlated to reduced TS formation, cell adhesion and spreading, identifying potential therapeutic benefit to the controlled reduction of Hsp90Î± for the deregulation of colon cancer characteristics. Given that Hsp27 and Î²-catenin are both involved in cell adhesion, cytoskeletal dynamics and interact directly with each other, we propose a role for targeting Hsp90Î± in the regulation cell adherence indirectly via reductions in levels of Î²-catenin and Hsp27, rather than by modifying the transcriptional activity of Î²-catenin.
Keywords: Heat shock proteins; Heat shock protein Hsp90 family; Colon (Anatomy) -- Cancer -- Treatment; Cell lines; Cancer stem-like cell; SW480; SW620